Early re-examination of chest CT may be unnecessary when patients with psittaci pneumonia at low and intermediate risk on Pneumonia Severity Index present with response to initial treatment - Chen, Ming; Zeng, Shu Ying; Lu, Sheng Jia; Shi, Miao; Zhang, Qing Qian (Frontiers in Medicine, 2025)
BackgroundChlamydia parrot pneumonia (CPS) is a rare community-acquired pneumonia (CAP) caused by Chlamydia parrot infection. With the development of metagenomic second-generation sequencing technology (mNGS), its diagnostic rate has improved in recent years. However, there are few clinical studies on Chlamydia parrot pneumonia, especially for patients with low and intermediate pneumonia severity index (PSI), and the necessity of early review of chest computed tomography (CT) is not clear. This study aimed to explore the clinical significance of early review of chest CT in patients with low and intermediate risk of Chlamydia parrot pneumonia with PSI after initial treatment was effective.MethodsRetrospective analysis of 8 patients with Chlamydia psittaci pneumonia diagnosed by metagenomic next-generation sequencing (mNGS) admitted to Zhejiang Provincial Tongde Hospital from January 2020 to December 2022 (PSI score ≤ 130 points). All patients had improved clinical symptoms and inflammatory markers after receiving antibiotic treatment, and chest CT was reexamined within 5-12 days. Evaluate the correlation between imaging changes before and after treatment and clinical symptoms and inflammatory indicators (CRP, PCT, WBC, etc.).ResultsAfter treatment, the patient’s body temperature, CRP, PCT and other indicators decreased significantly (P < 0.05). However, early CT reexamination showed that imaging progressed in 5 cases (62.5%), was stable in 2 cases (25%), and only 1 case (12.5%) showed partial improvement (P > 0.05). Nevertheless, none of the patients had a deterioration in their condition later on and finally achieved imaging recovery. Clinicians did not adjust the treatment plan when imaging progressed, and only 1 case was given glucocorticoid additionally.ConclusionFor patients with low- intermediate risk Chlamydia psittaci pneumonia with low PSI, if clinical symptoms and inflammatory markers improve, early reexamination of chest CT may have no additional clinical value and does not affect treatment decisions. Therefore, it is not recommended to routinely perform early CT re-examination for such patients to reduce unnecessary consumption of medical resources. Larger sample studies are needed in the future for further verification.Clinical trial registrationhttps://www.medicalresearch.org.cn/login, identifier MR-33-25003507.